Implementing Child-Friendly Teaching Methods to Improve Qur'an Reading Ability - Fauji, Imam; Fahyuni, Eni Fariyatul; Muhid, Abdul; Fahmawati, Zaki Nur (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2020)
As Qur'an serve as guidance in Muslim life, it goes without saying that there is an obligation for parents to teach their children the ability to read the Islamic holy book. On the part of school institution, educators are expected to offer interesting teaching methods to read Qur'an so that they have an ease to acquire the ability. This study was aimed at investigating the relationship between teaching methods and students' ability to read Qur'an. This study applied an action research to explore practical problems and to find some solutions to the problems encountered. The research subjects were 283 students of class VII at SMPN (Sekolah Menengah Pertama Negeri/State Junior High School) 2 Porong. This study collected data through: survey, observation, and semi-structured interviews. The findings show that students' ability to read Qur'an can be categorized into four levels namely: Ibtida 1, Ibtida 2, Jayyid, and Jayyid Jidan. Those four categories placed students based on their abilities in reading Qur'an. According to Pearson correlation, there was a significance value of 0.000 <0.05, which means there is a linear relationship between the teaching methods and the students' ability to read Qur'an. Following this result, some methods of learning to read Qur'an like Iqra, Tahqiq, TalaqqiÂ Mushafahah, and CMSA (Cara Mengaji Santri Aktif/an active way to read Qur'an for students) are in position to be applied in order to improve children's Qur'an reading abilities.